Effect of Processing on Nutritional and Antinutritional Composition of SAMPEA-11 and 20-T Cowpea Cultivars - Titus, Stephen Dio; Abershi, Ajiduku Leyoa; Francis, Achilus; Mafe, Alice Njolke; Samuel, Kennedy Banja; Daniel, Ejembi Ocholi; Ojogbene, Eleojo (Darul Yasin Al Sys, 2024)
This study investigates the effects of boiling and roasting on the nutritional and antinutritional composition of SAMPEA-11 and SAMPEA 20T. Ash content increased after roasting, with SAMPEA-11 rising from 2.5% to 3.1% and SAMPEA 20T from 2.7% to 3.4%. Crude fiber content displayed varied trend; in SAMPEA 20T an increase from 5.0% to 6.2% post-roasting, while SAMPEA-11 remained relatively stable. Lipid content increased significantly in roasted SAMPEA 20T by 2.8% and boiled SAMPEA-11 by 1.5. Protein content in SAMPEA-11 decreased after boiling and roasting, dropping by 4.5% and 2.9%, respectively. SAMPEA 20T showed an increase of 1.2 after boiling. For the antinutrients, boiling significantly reduced tannin levels in SAMPEA-11 from 0.45 mg/g to 0.23 mg/g, while roasting further reduced it to 0.15 mg/g in SAMPEA 20T. Oxalate levels increased after boiling, from 0.18 mg/g to 0.31 mg/g in SAMPEA-11 and 0.20 mg/g to 0.29 mg/g in SAMPEA 20T, while phytates decreased by 30% across both varieties after roasting. In the same vein, boiling and roasting both reduced concentrations lectin. While folate content, also decreased significantly in SAMPEA-11 after roasting, from 270 to 140 µg/100g. In contrast, SAMPEA 20T retained more folate, with a minimal reduction after boiling (250 to 220 µg/100g). Hence, Roasting was found to enhance shelf life by reducing moisture content while improving carbohydrate and mineral content. However, boiling appears more effective in retaining essential nutrients like protein and folate, especially in SAMPEA 20T. These findings provide insights for optimizing processing techniques to improve nutritional quality of cowpeas.